2012
DOI: 10.1073/pnas.1201794109
|View full text |Cite
|
Sign up to set email alerts
|

Folding pathways of proteins with increasing degree of sequence identities but different structure and function

Abstract: Much experimental work has been devoted in comparing the folding behavior of proteins sharing the same fold but different sequence. The recent design of proteins displaying very high sequence identities but different 3D structure allows the unique opportunity to address the protein-folding problem from a complementary perspective. Here we explored by Φ-value analysis the pathways of folding of three different heteromorphic pairs, displaying increasingly high-sequence identity (namely, 30%, 77%, and 88%), but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…In a more recent extensive study of the designed system Gianni and co-workers have shown that G A 88 folds using a robust transition state to a three helical bundle, while G B 88 folds over a very malleable energy landscape to a ubiquitin-like (mostly β-sheet) topology [79]. This malleability is assigned to the presence of multiple, competing foldons.…”
Section: Combining Experiments and Computational Studiesmentioning
confidence: 99%
“…In a more recent extensive study of the designed system Gianni and co-workers have shown that G A 88 folds using a robust transition state to a three helical bundle, while G B 88 folds over a very malleable energy landscape to a ubiquitin-like (mostly β-sheet) topology [79]. This malleability is assigned to the presence of multiple, competing foldons.…”
Section: Combining Experiments and Computational Studiesmentioning
confidence: 99%
“…It has been confirmed that the N and C termini in the conversion of G A to G B play a critical role in fold switching with hydrophobic core converting . The studies on the presence of an intermediate with reduced native contacts during the unfolding process from G B state to its unfolded state, and further investigations of the similar folding directions for G A 88 or G B 88 state have been performed by Gianni, Samuel, and co‐workers using equilibrium and kinetic folding/unfolding experiments, and molecular dynamics (MD) simulations . The folding mechanisms and stability for the G A 98, G B 98 states and their mutants were investigated using the free energy surface calculations and the all‐atom/coarse‐grained models .…”
Section: Introductionmentioning
confidence: 99%
“…The presented analysis concerns the well-known problem of correlating the protein's amino acid sequence with its 3D structure [1][2][3][4]. The search for algorithms which can be used to translate the former into the latter is a fundamental problem in proteomics [5,6] and often yields useful insight into the specific properties of individual proteins [7].…”
Section: Introductionmentioning
confidence: 99%